Analysis of the customer satisfaction based on the quality of service and catering as well as on the hotel facilities at Montana Del Cafe Kintamani Bali - Sukmana, Teja (SABA: Journal of Tourism Research, 2023)
This study explores how service excellence, culinary quality, and available amenities influence Customer Satisfaction at Montana Del Cafe Kintamani Bali. The research gathered data from customers who visited the cafe, using a sample of 90 individuals through an ad hoc sampling method. The analysis involved Descriptive Analysis, Validation Appraisal, Reliability Assessment, Statistical Tests (including Multiple Linear Regression, Partial Correlation Analysis, and more), all performed at a 95% confidence level. The study found that Service Excellence (X1) significantly influences customer satisfaction, with a positive t-test of 2.253 and a t-value of 0.257. Culinary quality (X2) also contributes to customer satisfaction, showing a positive but modest impact, with a t-test of 1.797 and a t-value of 0.213. Facilities (X3) have a strong positive effect on customer satisfaction, with a t-test of 4.980 and a t-value of 0.534. When analyzing all factors collectively,, Service Excellence (X1), Culinary Quality (X2), and Facilities (X3) harmoniously exerted a robust impact on Customer Satisfaction (Y) at Montana Del Cafe Kintamani Bali. This was confirmed through the formula Y = 0.286 + 0.257X1 + 0.213X2 + 0.534X3 and an F-test value of 60.076, since the F-table value (2.711) was surpassed at p0.05, the null hypothesis (Ho) was rejected, favoring the alternative hypothesis (Ha). Moreover, Determination Analysis demonstrated that collectively, Service Excellence (X1), Culinary Quality (X2), and Facilities (X3) contributed significantly, accounting for 67.7% of the variance in Customer Satisfaction (Y) at Montana Del Cafe Kintamani Bali. In conclusion, Service Excellence (X1) and Facilities (X3) distinctly and meaningfully foster Customer Satisfaction (Y), while the impact of Culinary Quality (X2), although positive, remains relatively modest.